PERANAN UPAYA HUKUM TERHADAP PENEGAKKAN HUKUM STUDI KASUS : KASUS DIVESTASI SAHAM PT.KPC DI KUTAI TIMUR - Sudiran, FL. (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
The aim of this research is to keep the supremacy of law in East Kalimantan. The background ofÂ  it is that there is a corporate corruption crime case which has happened in this province which must be focused on the legal material proof. The method of this research is qualitative one. The location of it is in Samarinda, in June 2013. The data is taken from Tribun daily newspaper here dated on June 2, 3, 5 and 16. The persons accused are AN (Senior Director) of PT. Kutai Timur Energi (KTE) dan ATW (Director of PT. Kutai Timur Energi (KTE). Those persons concerned are found guilty. The result of the research is that those persons accused above have been made some efforts to make themselves innocent. The last effort for them is judicial review of the court if they have some new proofs or novum on it.Â